Uncinate Duct Dilation in Intraductal Papillary Mucinous Neoplasms of the Pancreas: A Radiographic Finding with Potentially Increased Malignant Potential - Ammori, John B (J Gastrointest Surg, 2014)
BACKGROUND: Risk of high-grade dysplasia and invasive carcinoma in intraductal papillary mucinous neoplasms (IPMN) of the pancreas is increased in main-duct compared to branch-duct lesions. We hypothesized that isolated uncinate duct dilation may also be a radiographic indicator of high-risk disease as the primary drainage of this portion of the gland originates from a distinct embryologic precursor. METHODS: All patients with available preoperative imaging who underwent resection for IPMN between 1994 and 2010 were included (n=184). Imaging studies were reviewed by an experienced radiologist who was blinded to the pathologic results, and studies were categorized as main-duct, branch- duct, or combined-duct. The presence of uncinate duct dilation was assessed as a risk factor for tumors which proved to have high-grade dysplasia (HGD) or invasive carcinoma (IC) on pathologic assessment. RESULTS: IPMN with HGD or IC were identified in 82 of 184 cases (45%). Without considering uncinate duct dilation, IPMN with HGD or IC were present in 84% of patients with main-duct IPMN (n= 31/37), 58% with combined-duct IPMN (n= 23/40), and 26% with branch-duct IPMN (n=28/107). Dilation of the uncinate duct was observed in 47 patients, with or without main duct dilation, and 30 of these (64%) contained HGD or IC on pathology. Isolated uncinate duct dilation without main duct dilation was observed in 17 patients, and 11 (65%) had HGD. On multivariate analysis of IPMN without associated main-duct dilation, uncinate duct dilation was independently associated with IPMN with HGD or IC (p=0.002). CONCLUSION: Uncinate duct dilation on preoperative radiologic imaging appears to be an additional risk factor for IPMN-associated high-grade dysplasia or adenocarcinoma.